Furniture collapsible design optimization using spatial geometric analysis - Qiu, Qi; Dong, Manman (Applied mathematics and nonlinear sciences, 2024)
In this paper, the function, style, and material of foldable furniture are designed, and the process of selecting, generating, and deforming the blocks is combined with parametric techniques to model the foldable furniture blocks. To generate shrinkable unfolded furniture, the objective function of the foldable furniture is optimized, combined with the optimization algorithm of Voronoi polygon and surface parameterization, and the spatial geometry results of the foldable furniture are optimized using spatial geometry. After analyzing the optimized foldable furniture, it was concluded that the overall mechanical strength index was greater than 0.76, and the optimized weight, fluidity, operational complexity, material, degree of structural wear, and node stability were all significant factors exceeding 0.7.